Multispecies Purification of Testicular Germ Cells. Issue 4 (1st October 2016) - Lima, Ana C.; Jung, Min; Rusch, Jannette; Usmani, Abul; Lopes, Alexandra M.; Conrad, Donald F.
Abstract: Advanced methods of cellular purification are required to apply genome technology to the study of spermatogenesis. One approach, based on flow cytometry of murine testicular cells stained with Hoechst-33342 (Ho-FACS), has been extensively optimized and currently allows the isolation of nine germ cell types. This staining technique is straightforward to implement, is highly effective at purifying specific germ cell types, and yields sufficient cell numbers for high-throughput studies. Ho-FACS is a technique that does not require species-specific markers, but whose applicability to other species is largely unexplored. We hypothesized that, because of the similar cell physiology of spermatogenesis across mammals, Ho-FACS could be used to produce highly purified subpopulations of germ cells in mammals other than mouse. To test this hypothesis, we applied Ho-FACS to four mammalian species that are widely used in testis research: Rattus norvegicus, Cavia porcellus, Canis familiaris, and Sus scrofa domesticus . We successfully isolated four germ cell populations from these species with average purity of 79% for spermatocytes, 90% for spermatids, and 66% for spermatogonia. Additionally, we compare the performance of mechanical and chemical dissociation for each species, and propose an optimized gating strategy to better discriminate round and elongating spermatids in the mouse, which can potentially be applied to other species. Our work indicates that spermatogenesis may be uniquely accessible among mammalian developmental systems, as a single set of reagents may be sufficient to isolate germ cell populations from many different mammalian species, opening new avenues in the fields of development and male reproductive biology.